Disentangling the relative effects of soil moisture and vapor pressure deficit on photosynthesis in dryland Central Asia. (April 2022) - Yu, Tao; Jiapaer, Guli; Bao, Anming; Zheng, Guoxiong; Zhang, Junfeng; Li, Xu; Yuan, Ye; Huang, Xiaoran; Umuhoza, Jeanine
Highlights: Decoupling of soil moisture and vapor pressure deficit by sorting and binning. Soil moisture promoted photosynthesis in 94% of the vegetation areas. Vapor pressure deficit inhibited photosynthesis in 60% of the vegetation areas. Photosynthesis is dominated by soil moisture in Central Asia. Abstract: Soil moisture (SM) and vapor pressure deficit (VPD) are key factors affecting photosynthesis, and quantifying their effects on this process can help us to understand the mechanisms of carbon cycling in terrestrial ecosystems. However, the strong coupling of SM and VPD makes it difficult to quantify their relative importance in the ecosystem carbon cycle. In this study we decoupled the negative correlation between SM and VPD by sorting and binning reanalysed SM and VPD data, and based on this, we quantified the relationship between VPD and SM and sunlight-induced chlorophyll fluorescence (SIF) in dryland Central Asia (CA). We found that SM promoted and suppressed photosynthesis in CA, accounting for 94.08% and 5.92% of the vegetated areas in CA, respectively; VPD promoted and suppressed photosynthesis in CA accounted for 39.68% and 60.32% of the vegetation area, respectively. The effects of SM and VPD on the photosynthesis of different vegetation types were different: the photosynthesis of croplands and forests tended to increase and then decrease with increasing SM, and the photosynthesis of grasslands, shrublands and sparse vegetation tended to increase with increasing SM; the photosynthesis of croplands, grasslands and forests increase with VPD, while the opposite is true for shrublands and sparse vegetation. Relative effects on photosynthesis indicated that the areas where SM had a greater effect than VPD on photosynthesis accounted for 74.26% of the vegetation area, mainly in the central part of Kazakhstan and Kyrgyzstan, which was related to the fact that the main vegetation types in these regions were croplands, grasslands, forests and sparse vegetation. The areas with greater effects of VPD than SM on photosynthesis were mainly located in the northern part of Kazakhstan and most of Uzbekistan and Turkmenistan (25.74% of vegetated areas). Our study contributes to further understanding of the key processes involved in carbon cycling in terrestrial ecosystems.